Economic analysis using higher frequency time series: Challenges for seasonal adjustment - Daniel Ollech (Deutsche Bundesbank, 2021)
The COVID-19 pandemic has increased the need for timely and granular information to assess the state of the economy in real time. Weekly and daily indices have been constructed using higher frequency data to address this need. Yet the seasonal and calendar adjustment of the underlying time series is challenging. Here, we analyse the features and idiosyncracies of such time series relevant in the context of seasonal adjustment. Drawing on a set of time series for Germany - namely hourly electricity consumption, the daily truck toll mileage, and weekly Google Trends data - used in many countries to assess economic development during the pandemic, we discuss obstacles, difficulties, and adjustment options. Furthermore, we develop a taxonomy of the central features of seasonal higher frequency time series.
Keywords: C14; C22; C87; E66; 330; COVID-19; DSA; Calendar adjustment; Time series characteristics